STK25 protein mediates TrkA and CCM2 protein-dependent death in pediatric tumor cells of neural origin - Costa, Barbara; Eils, Roland; König, Rainer (The journal of biological chemistry, 2012)
The TrkA receptor tyrosine kinase induces death in medulloblastoma cells via an interaction with the cerebral cavernous malformation 2 (CCM2) protein. We used affinity proteomics to identify the germinal center kinase class III (GCKIII) kinases STK24 and STK25 as novel CCM2 interactors. Down-modulation of STK25, but not STK24, rescued medulloblastoma cells from NGF-induced TrkA-dependent cell death, suggesting that STK25 is part of the death-signaling pathway initiated by TrkA and CCM2. CCM2 can be phosphorylated by STK25, and the kinase activity of STK25 is required for death signaling. Finally, STK25 expression in tumors is correlated with positive prognosis in neuroblastoma patients. These findings delineate a death-signaling pathway downstream of neurotrophic receptor tyrosine kinases that may provide targets for therapeutic intervention in pediatric tumors of neural origin.
Gesehen am 04.10.2018